2014
DOI: 10.4238/2014.september.26.14
|View full text |Cite
|
Sign up to set email alerts
|

Independent and joint effects of the IL-6 and IL-10 gene polymorphisms in pulmonary tuberculosis among the Chinese Han population

Abstract: ABSTRACT. We investigated the association between interleukin (IL)-6 and IL-10 gene polymorphisms and the susceptibility to pulmonary tuberculosis (PTB). DNA samples were obtained from 191 Han Chinese patients with PTB and 191 healthy control subjects. and IL-10 (-1082, -819) polymorphisms were analyzed using polymerase chain reaction-restriction fragment length polymorphism. The IL-6 -572 C/C and IL-10 -819 T/T genotypes were observed less frequently in the case group than in the control group, with crude od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…Previous studies have reported that cytokine genes contribute to susceptibility of TB, such as interferon-1β, interleukin (IL)-3, IL-6, IL-10, and IL-12B IL-17 as well as IL-18 (Selvaraj et al, 2008;Abhimanyu et al, 2011;Meenakshi et al, 2013;Feng et al, 2014;Tiwari et al, 2014;Zhang et al, 2014). However, the results have been inconsistent.…”
Section: Introducioncontrasting
confidence: 40%
“…Previous studies have reported that cytokine genes contribute to susceptibility of TB, such as interferon-1β, interleukin (IL)-3, IL-6, IL-10, and IL-12B IL-17 as well as IL-18 (Selvaraj et al, 2008;Abhimanyu et al, 2011;Meenakshi et al, 2013;Feng et al, 2014;Tiwari et al, 2014;Zhang et al, 2014). However, the results have been inconsistent.…”
Section: Introducioncontrasting
confidence: 40%
“…Among the included publications, eight evaluated the association between the IL-6 (−174G/C) polymorphism and tuberculosis risk, with 959 cases and 1608 controls; 7 , 18 , 25 – 30 three focused on IL-6 (−572C/G) polymorphism, including 686 cases and 725 controls. 17 , 32 , 33 One article assessed both IL-6 (−174G/C) and (−572C/G) with 495 cases and 358 cases, 18 and it was treated as two independent studies in the present meta-analysis. Consequently, 13 studies were available for analyzing the association between IL-6 gene polymorphism and tuberculosis risk, nine (8 publications) of them were conducted in Asians, 17 , 18 , 25 , 27 , 29 , 30 , 32 , 33 while two were in Caucasians, 26 , 28 and two were in Latinos.…”
Section: Resultsmentioning
confidence: 99%
“…17 , 32 , 33 One article assessed both IL-6 (−174G/C) and (−572C/G) with 495 cases and 358 cases, 18 and it was treated as two independent studies in the present meta-analysis. Consequently, 13 studies were available for analyzing the association between IL-6 gene polymorphism and tuberculosis risk, nine (8 publications) of them were conducted in Asians, 17 , 18 , 25 , 27 , 29 , 30 , 32 , 33 while two were in Caucasians, 26 , 28 and two were in Latinos. 7 , 31 Ten studies (9 publications) recruited pulmonary tuberculosis patient, 17 , 18 , 25 , 27 32 three investigated other types of tuberculosis such as tuberculous pleurisy, renal tuberculosis, tuberculous lymphadenitis, and central nervous system tuberculosis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, expression of miR-31 expression was negatively correlated with serum levels of the innate immunity cytokines IL-6, TNF-α, NF-κB, and IFN-γ. IL-6 is secreted by Toll-like receptor 2-expressing cells during early MtB infection, and is involved in anti-tuberculosis immunity (Feng et al, 2014). TNF-α increases the capacity of macrophages to phagocytose and stimulates macrophages apoptosis, which leads to increased presentation of mycobacterial antigens by dendritic cells (Cavalcanti et al, 2012).…”
Section: Discussionmentioning
confidence: 99%